On Weak Exponential Expansiveness of Evolution Families in Banach Spaces - Tian Yue; Xiao-qiu Song; Dong-qing Li (The Scientific World Journal)
The aim of this paper is to give several characterizations for the property of weak exponential expansiveness for evolution families in Banach spaces. Variants for weak exponential expansiveness of some well-known results in stability theory (Datko (1973), Rolewicz (1986), Ichikawa (1984), and Megan et al. (2003)) are obtained.